Assessment of the quality of the management of childbirth by vaginal delivery in 5 reference maternity clinics in Dakar, Senegal - Gassama, Omar; Faye Dieme, Marie Edouard; Niang, Mouhamadou Mansour; Diallo, Moussa; Diouf, Abdoul Aziz; Ndiaye, Abdou; Gueye, Mamour; Moreira, Philippe Marc; Diouf, Alassane; Moreau, Jean Charles (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: The current strategy to fight maternal and perinatal mortalities is mainly based on three pillars: family planning, skilled delivery and emergency obstetric and neonatal cares. The objective of the study was to assess the quality of the management of low-risk deliveries in 5 reference maternity clinics in the region of Dakar. Methods: This is an observation-based multicentric, prospective and descriptive study, carried out over a four-month period, from September 1st to December 31st, 2012, in 5 reference maternity hospitals in the region of Dakar. For each delivery, the focus was put on parturient socio-demographic features, the surveillance techniques of the labour, the handling of the exit and delivery phases, materno-fetal complications but also on the new-born care. To assess the quality of childbirth management, a comparison between the practices was made and observed on the field and the World Health Organization’s recommendations which fall into 4 categories (A, B, C and D) depending on the appropriateness or not of their use. For data input and analysis, we used the 13.0 version of the SPSS software. Results: During the study period, 200 childbirths were observed. The epidemiologic profile used for this study was that of a literate woman with a low record of childbirth who was 27 on average with a mean parity of 3. Forty seven percent of childbirth deliveries were observed in Roi Baudouin hospital centre. The A-category recommendations of the World Health Organization, such as the consumption of drinks, mobility during labour, the use of a partograph, the active management of the third stage of labour (AMTSL) and the examination of the placenta were applied in 22.5%, 86.2%, 23.4%, 100% and 23.4% of cases respectively. As for the B-category recommendations, which recommend the removal of those practices deemed harmful such as the back position during labour, the placement of an intravenous line and the oxytocin infusion, they were carried out in 91.84%, 98.08% and 7.28% of cases respectively. C and D categories which deal with non-recommended practices such as the use of abdominal expressions during labour and episiotomy were used in 47.6% and 39.7% of cases respectively. Conclusions: In our study, the most followed A-category recommendations from the WHO are: encouraged mobility, the use of single-use equipment, AMTSL and skin-on-skin contact. However, some B, C and D-category practices are still widely used in our maternity hospitals. The health authorities should make sure that the WHO recommendations are followed.